Source apportionment of PM2.5 and PM10 by Ionic and Mass Balance (IMB) in a traffic-influenced urban atmosphere, in Portugal. (15th February 2020) - Pio, C.; Alves, C.; Nunes, T.; Cerqueira, M.; Lucarelli, F.; Nava, S.; Calzolai, G.; Gianelle, V.; Colombi, C.; Amato, F.; Karanasiou, A.; Querol, X.
Abstract: The recently developed Ion and Mass Balance (IMB) source apportionment methodology was applied to a traffic influenced urban aerosol, permitting the quantification of the contributions of 11 source components, or formation processes, which accounted for more than 96% of the measured aerosol mass loading. Main sources included exhaust and non-exhaust road vehicle emissions, biomass burning, secondary inorganic and organic pollutants, and primary soil and sea salt emissions. While in summer secondary carbonaceous matter is the predominant fraction, in winter biomass burning accounts, on average, for more than 40% of the PM2.5 aerosol. Comparison with Positive Matrix Factorization (PMF) showed the complementary characteristics of the two methodologies. PMF yielded 8 source profiles, including industry and oil combustion sources not discriminated by IMB. PMF is better at quantifying multiple component contributions to sources. IMB solves problems of collinearity between aerosol tracers and permits the discrimination of secondary formed pollutants. Highlights: The urban aerosol has high levels of carbonaceous matter. In winter biomass burning dominates the aerosol loading. IMB discriminated 11 processes or sources of the aerosol. IMB compares well with PMF in aerosol apportionment.